EFFECTIVENESS OF TEACHING SOCIAL STUDIES THROUGH KINESTHETICS METHOD FOR ENHANCING STUDENTS’ ACADEMIC PERFORMANCE - Zarrin Taj Hina; Sadia Jahan; Ayesha Ayaz (International Journal of Contemporary Issues in Social Sciences, 2024)
This thesis, which focuses on grade 6 pupils at The Ceder School in Karachi, Pakistan, investigates the efficacy of the kinesthetic technique in raising academic performance and interest in social studies. We used the kinesthetic approach to teach five lessons on pollution-related subjects, such as "Importance of Recycling" and "Effect of Pollution on Plants, Human Health and Environment." A pre-test and post-test were administered to the 16 students (eight girls and eight boys) in the study in order to gauge academic progress. As demonstrated by the pre-test results, the experimental group outperformed the control group, scoring an average of 46.2% in the post-test compared to the control group’s 34.7% in the pre-test. In addition, a comparison of the experimental and control groups’ post-test results showed that the experimental group had a marginal advantage, scoring 94.3% as opposed to 93.7% for the control group. According to these results, the kinesthetic approach considerably improves social studies students’ critical thinking, problem-solving abilities, and level of involvement. This study’s conclusion affirms that kinesthetic learning has the potential to be a powerful teaching method in the twenty-first century, encouraging students to participate more actively in class and get a deeper comprehension of the material. This study adds to the continuing conversations in educational theory by showing how important it can be to improve student outcomes through practical, hands-on learning, especially in courses like social studies where students gain from active, real-world exploration. Schools should incorporate kinesthetic learning techniques not only in social studies but also in other subjects. Although the kinesthetic approach is very successful, it should be used in conjunction with more conventional teaching techniques in order to meet the needs of diverse learners and offer a comprehensive education.